Analysis and suggestion of future 5G directions - Shanzhi CHEN (Dianxin kexue)
Firstly,the global research progress of 5G was briefly introduced,and the requirements and challenges of 5G were analyzed.The understanding and views on 5G were shared,and 5G was pointed out as an internet of things generation,a telecom IT generation,software definition and cloud generation,a cellular structure transition generation,and serving as a link between the past and the future generation.Then,the key technologies of 5G wireless transmission and network were also analyzed,including PDMA,UUDN and virtual RAT technologies,which were proposed by the author's team.Particularly,the advantages of TDD in 5G was pointed,and the new air interface of 5G adopting TDD mode was predicted.At last,combined with China's innovative experience in TD-SCDMA and TD-LTE,suggestions on how to develop 5G in China were provided.